All-out test in tethered canoe system can determine anaerobic parameters of elite kayakers - Messias, L. H. D.; Ferrari, H. G.; Sousa, F. A. B.; dos Reis, I. G. M.; Serra, C. C. S.; Gobatto, C. A.; Manchado-Gobatto, F. B. (International Journal of Sports Medicine, 2015)
The aims of this study were to use a specific all-out 30-sec tethered test to determine the anaerobic parameters in elite kayakers and verify the relationship between these results and sports performance. Twelve elite slalom kayakers were evaluated. The tethered canoe system was created and used for the all-out 30-sec test application. Measurements of peak force, mean force, minimum force, fatigue index and impulse were performed. Performance evaluation was determined by measuring the time of race in a simulated race containing 24 gates on a white-water course. Blood was collected (25-µl) for analysis of lactate concentration at rest and at 2, 4, 6, 8 and 10-min intervals after both the all-out test and the simulated race. The Pearson product moment correlation shows a inverse and significant relationship of peak force, mean force and impulse with time of race. Blood lactate concentrations after the all-out test and the simulated race peak at same time (4 min). Additionally, no interaction was visualized between time and all-out test/simulated race for blood lactate concentrations (P <0.365). These results suggest a relationship between the parameters of the all-out test and performance. Thus, the tethered canoe system is a useful tool for determining parameters that could be used in training control of slalom kayakers.